Effects of alcohol on the fetus: impact and prevention. - Little, R. E. (1981)
In the spectrum of adverse effects on the fetus or infant associated with maternal drinking during pregnancy the most dramatic is the fetal alcohol syndrome, a pattern of malformation that has been associated with maternal alcohol abuse. Other undesirable outcomes of pregnancy linked to alcohol exposure in utero include growth deficiency, major and minor anomalies, decrements in mental and motor performance, and fetal and perinatal wastage. Alcohol, like other teratogens, does not uniformly affect all those exposed to it. Rather, there seems to be a continuum of effects of alcohol on the fetus with increasingly severe outcomes generally associated with higher intakes of alcohol by the mother. The cost of fetal damage associated with alcohol exposure is very high. A program to decrease the incidence of fetal alcohol effects is therefore imperative. The cornerstone of such a program must be not only education of the public but also careful training of all professionals who provide health care for pregnant women.